Оцінка Г. В. Адамовичем творчості І. О. Буніна на сторінках паризького «Звєна» (1924–1926 рр.) (Літератури світу: поетика, ментальність і духовність, 2016)
In Paris «links» Pluzhnik published four articles about the works of Bunin and many times mentioned his work in connection with the consideration of literary texts by other authors. In the article, referring to the Adamovich’s evaluation of Bunin’s creativity at the pages of Paris «links», author draws attention to the unconditional critic’s acceptance of the writer’s work, and to the proximity of their worldviews. Adamovich, as well as Bunin does not accept the artificial decadence, artificiality and falseness experiences. Adamovich transmits personal experience of reading, stressing that he did not have enough words to fully appreciate this or that writer’s book.
Keywords: декаданс; критика; оцінка; рецепція; стаття